Agro-Industry Management to Improve Productivity and Quality for Sustainable Growth by Smart Farming - Narusinghsamran, Krit; Silpcharu, Thanin (Princess of Naradhiwas University Journal, 2021)
Digital transformation plays a vital role for an agro-industry to adapt themselves to increase its productivity. It leads into the idea of smart farming to uplift the agro-industry to its sustainable growth in economic and society. The objectives of this research were to study traditional agro-industry management and ways to manage smart argo-industry in order to increase the productivity and quality to reach sustainable growth. Also, the research aimed to develop structural equation model for smart argo-industry management. The research was conducted in both quantitative and qualitative. Survey and interview were conducted with 500 representatives who involved in building values in a large, a medium and a small agro-industry business sectors, living in southern, central, northern, northeastern and eastern regions of Thailand. The samples were selected using descriptive statistics and reference statistics The results of this research revealed that the knowledge aspect such as establishing an agency for knowledge management should be focused. The innovation aspect should include encouraging innovation professionals to research new concepts in information technology, for example, encouraging to provide opportunities for information exchange of smart farming with other agencies. For the resource aspect, it should select personnel with expertise in smart agriculture to work with the organization. The process management aspect should include the analysis and in-dept examination of quality of work at every level in order to assess the capability of the department. Last, the analysis of structural equation model found that the evaluation was consistent with the empirical data (CMIN-p = .056) (CMIN/DF = 1.111) (GFI = .942) and (RMSEA = .015)